Design of guidance and control systems for tactical missiles - Zaikang, Qi; Defu, Lin (Boca Raton : CRC Press, 2020)
Design of Guidanceand Control Systems for Tactical Missiles presents a modern, comprehensive study of the latest design methods for tactical missile guidance and control. It analyzes autopilot designs, seeker system designs, guidance laws and theories, and the internal and external disturbances affecting the performance factors of missile guidance control systems. The text combines detailed examination of key theories with practical coverage of methods for advanced missile guidance control systems. It is valuable content for professors and graduate-level students in missile guidance and control, as well as engineers and researchers who work in the area of tactical missile guidance and control.
Table of Contents1. The Basics of Missile Guidance Control1.1. Overview1.2. Missile Control Methods 2. Missile Trajectory Models, Aerodynamic Derivatives, Dynamic Coefficients and Missile Transfer Functions2.1 Symbols and Definitions 2.2 Euler Equations of the Missile Rigid Body Motion 2.3 Configuration of the Control Surfaces 2.4 Aerodynamic Derivatives and the Missile Control Dynamic Coefficient 2.5 The Transfer Function of a Missile the Object Being Controlled 3. Basic Missile Control Component Mathematics Models3.1 Seeker 3.2 Actuator 3.3 Angular Rate Gyro 3.4 Accelerometer 3.5 Inertial Navigation Components and Integrated Inertial Navigation Module 4. Autopilot Design4.1 Acceleration Autopilot 4.2 Pitch/Yaw Attitude Autopilot 4.3 Flight Path Angle Autopilot 4.4 Roll Attitude Autopilot 4.5 BTT Autopilot 4.6 Thrust vector control and thruster control 5. Guidance radar5.1 Introduction 5.2 Motion Characteristic of the Target Line-of-Sight 5.3 Loop of the Guidance Radar Control 5.4 Effect of the Receiver Thermal Noise on the Performance of GuidanceRadar5.5 Effect of Target Glint on the Performance of Guidance Radar 5.6 Effect of Other Disturbances on the Performance of Guidance Radar 6. Line of Sight Guidance6.1 LOS Guidance System6.2 Analysis of the Required Acceleration for the Missile with LOSGuidance6.3 Analysis of the LOS Guidance Loop6.4 Lead Angle Method 7. Seekers7.1 Overview7.2 Electromechanical Structure of Commonly Used Seekers7.3 Mechanism Analysis of the Anti-disturbance Moment of the Seeker'sStabilization Loop and Tracking Loop 7.4 Transfer Function of Body Motion Coupling and Parasitic Loop7.5 A Real Seeker Model 7.6 Other Parasitic Loop Models 7.7 Stabilization Loop and Tracking Loop Design of the Platform BasedSeeker 8. Proportional Navigation and Extended Proportional Navigation Guidance Laws 8.1 Proportional Navigation Guidance Law 8.2 Extended Proportional Navigation Guidance Laws (Optimal Proportional Navigation, OPN) 8.3 Other Types of Proportional Navigation Laws8.4 Target Maneuver Acceleration Estimation8.5 Optimum Trajectory Control DesignAppendix. I Proof of the Proportional Navigation Law with the Help of Optimal Control TheoryAppendix. II Adjoint MethodBibliographyIndex
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Electricity; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Mechanical; Guided missiles -- Control systems; Guided missiles -- Guidance systems